2017
DOI: 10.31234/osf.io/j2cp6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Why do you ask? The informational dynamics of questions and answers

Abstract: Asking questions is one of our most efficient and reliable means of learning about the world. Yet we do not often pose these questions to an impartial oracle; we ask cooperative social partners, in dialogue. In this paper, we aim to reconcile formal models of optimal question asking and answering with classic effects of social context. We begin from the observation that question-answer dialogue is motivated by a two-sided asymmetry in beliefs: questioners have a private goal but lack goal-relevant information … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 73 publications
(106 reference statements)
0
11
0
Order By: Relevance
“…The Rational Speech Acts (RSA) framework is a family of computational models of communication (Frank & Goodman, 2012) where two rational agents, a speaker and a listener, are modeled as recursively reasoning about each other when producing and interpreting utterances. This work follows important precedents from game theory (Lewis, 1969;Jager, 2007;Franke, 2009;Golland et al, 2010), and has been shown to capture a wide range of linguistic phenomena (e.g., Goodman and Stuhlmüller, 2013;Kao et al, 2014;Hawkins and Goodman, 2017;van Tiel et al, 2021).…”
Section: Rational Speech Acts (Rsa) Frameworkmentioning
confidence: 91%
“…The Rational Speech Acts (RSA) framework is a family of computational models of communication (Frank & Goodman, 2012) where two rational agents, a speaker and a listener, are modeled as recursively reasoning about each other when producing and interpreting utterances. This work follows important precedents from game theory (Lewis, 1969;Jager, 2007;Franke, 2009;Golland et al, 2010), and has been shown to capture a wide range of linguistic phenomena (e.g., Goodman and Stuhlmüller, 2013;Kao et al, 2014;Hawkins and Goodman, 2017;van Tiel et al, 2021).…”
Section: Rational Speech Acts (Rsa) Frameworkmentioning
confidence: 91%
“…It effectively coarse-grains the set of possible worlds, allowing the speaker and listener to ignore irrelevant details. RSA-based models have integrated the notion of a QUD (Goodman & Lassiter, 2015) to explain interpretation of nonliteral or vague language in various forms (Hawkins et al, 2015;Kao & Goodman, 2015;Kao, Wu, et al, 2014;Lassiter & Goodman, 2017;Yoon et al, 2020). This document is copyrighted by the American Psychological Association or one of its allied publishers.…”
Section: Truthfulness Relevance and Speaker Goalsmentioning
confidence: 99%
“…Conversely, speakers can use the same principles to select information that maximally improves the listener's decision making (Benz, 2006;Benz & Van Rooij, 2007). This can be seen when speakers "go beyond" the literal content of a question and supply additional decision-relevant knowledge (Hawkins et al, 2015). For example, asked if they accepted credit cards, restaurant owners answered the question and then spontaneously informed the caller about unexpected closures: "Uh, yes, we accept credit cards.…”
Section: Implications For Psychologymentioning
confidence: 99%
“…Our key modeling innovation lies in building issues into these models. In this, we are inspired by linguistic work on question-sensitive RSA (Goodman and Lassiter, 2015;Hawkins and Goodman, 2019).…”
Section: Issues Target Captionmentioning
confidence: 99%
“…Each cell represents a possible resolution of the issue. These ideas are brought into RSA by Goodman and Lassiter (2015) and Hawkins and Goodman (2019). We translate those ideas into the models for ISIC (Section 4), where an issue takes the form of a partition over a set of natural images.…”
Section: Issue-sensitivity In Languagementioning
confidence: 99%